Unilateral extrafoveal choroidal neovascularization in a 13-year-old child with bilateral optic nerve drusen - Jędrzejczak-Stróżniak, Monika; Siwiec-Prościńska, Joanna; Gotz-Więckowska, Anna; Kocięcki, Jarosław (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Aim: The aim of our research was to describe the effect of an off-label intravitreal ranibizumab injection for treatment of unilateral extrafoveal choroidal neovascularization a with bilateral optic nerve drusen. Material and methods: 13-year-old girl presented with decreased visual acuity of her left eye and optic nerve drusen confirmed by B-scan ultrasound examination in both eyes. Fluorescein angiography and optical coherence tomography revealed the presence of choroidal neovascularization in the left eye. The patient was treated with a single injection of ranibizumab and monitored by clinical examination, optical coherence tomography and fluorescein angiography. Results: Choroidal neovascularization was successfully treated and the best corrected visual acuity (Snellen) fully recovered from 20/50 to 20/20 over a period of 2 months. After this time at the 30 months follow-up, visual acuity and fundus were stable without the recurrence of choroidal neovascularization. Conclusions: Optic nerve drusen should be taken into account and carefully observed as a possible cause of peripapillary choroidal neovascularization in children. Ranibizumab can be a successful off-label treatment in children suffering from choroidal neovascularization associated with optic nerve drusen.